The Utility of Point-of-Care Ultrasound in the Pediatric Intensive Care Unit. (August 2022) - Watkins, Laura A.; Dial, Sharon P.; Koenig, Seth J.; Kurepa, Dalibor N.; Mayo, Paul H.
Objectives: Point of care ultrasound (POCUS) in adult critical care environments has become the standard of care in many hospitals. A robust literature shows its benefits for both diagnosis and delivery of care. The utility of POCUS in the pediatric intensive care unit (PICU), however, is understudied. This study describes in a series of PICU patients the clinical indications, protocols, findings and impact of pediatric POCUS on clinical management.Design: Retrospective analysis of 200 consecutive POCUS scans performed by a PICU physician.Patients: Pediatric critical care patients who required POCUS scans over a 15-month period.Setting: The pediatric and cardiac ICUs at a tertiary pediatric care center.Interventions: Performance of a POCUS scan by a pediatric critical care attending with advanced training in ultrasonography.Measurement and Main Results: A total of 200 POCUS scans comprised of one or more protocols (lung and pleura, cardiac, abdominal, or vascular diagnostic protocols) were performed on 155 patients over a 15-month period. The protocols used for each scan reflected the clinical question to be answered. These 200 scans included 133 thoracic protocols, 110 cardiac protocols, 77 abdominal protocols, and 4 vascular protocols. In this series, 42% of scans identified pathology that required a change in therapy, 26% confirmed pathology consistent with the ongoing plans for new therapy, and 32% identified pathology that did not result in initiation of a new therapy.Conclusions: POCUS performed by a trained pediatric intensivist provided useful clinical information to guide patient management.